Pengaruh Kebijakan Ekonomi Publik Terhadap Iklim Investasi di Negara Berkembang - Harahap, Sherli Inggriani; Mutmainnah, Siti; Anggraeni, Reni; M, Melda; Anjani, Chairunissa Puti; A, Alfikritullah; Putra, Zakhira Ramdana; Herdiana, Dian (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Public economic policies play an important role in creating a conducive investment climate in developing countries. This study aims to analyze how fiscal, monetary, and public regulatory policies affect the attractiveness of investment, both domestic and foreign. Using a descriptive qualitative approach through literature studies and secondary data, this article examines various government policies, ranging from subsidies, fiscal incentives, infrastructure development, to regulatory reform. The results of the study indicate that macroeconomic stability, legal clarity, and bureaucratic efficiency are key factors in attracting investors. On the other hand, regulatory inconsistency and economic uncertainty have proven to be major obstacles. Therefore, the formulation of measurable and sustainable public economic policies is an absolute requirement in improving the investment climate in developing countries.